Love from Godzilla - Luchini, Olivia; Bradley, Jordan; Moore, Milo (New York Penguin Young Readers Licenses, an imprint of Penguin Random House LLC, 2023)
"The King of the Monsters shows all the things that love is in this perfect book for Valentine's Day that features illustrations of everyone's favorite kaijus"--
112850
Keywords: Godzilla -- (Fictitious character) -- Juvenile fiction; Monsters -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Love -- Juvenile fiction; Picture books; Picture books